Investigation of a Protein Encoded by a Gene of Mus musculus and relating it to an Orthologous Protein in Homo sapiens - Mallick, Avijit (International Journal of Pharmaceutical and Life Sciences, 2013)
The gene of Mus musculus was cloned into plasmid vector (pYEUra3) of E.coli from the cDNA library which was then verified using colony PCR. The plasmid DNA was then purified and digested with EcoRI to check the presence of an insert. PICOGREEN assay, HindIII digestion and absorbance were used to quantify the DNA. The purified DNA was then sequenced and searched using different databases to find a match. Finally, the protein of interest was identified to be Sentrin-specific protease 2(SUMO-1 protease 1 ) which processes SUMO precursor into their mature form and also causes deSUMOylation from their target substrate. DOI: http://dx.doi.org/10.3329/ijpls.v2i1.15131 International Journal of Pharmaceutical and Life Sciences Vol.2(1) 2013: 10-21